Determinan Non Performing Loan (NPL) pada Industri Perbankan (Bukti Empiris Perusahaan Go Publik di Bursa Efek Indonesia) - Kamaludin, .; Darmansyah, .; Usman, Berto (Universitas Brawijaya, Indonesia, 2015)
Abstract: This study aims to identify the determinant factors of Non Performing Loan (NPL)in Indonesian banking sector. Data were collected from 16 banks by observation during theyear 2002 to 2011. From the data found that there were six variables which closely associatedto the variation of NPL for the subsequent observation period. In addition, the sampleswere taken from public listed company in Indonesia stock exchange, in which the particulardata were imported from Indonesian Capital Market Directory (ICMD CD-ROM). The furtheranalysis was conducted by employing Pooled EGLS (Cross-section random effects). Ourresults reflected that NPL was obviously driven by the volatility and fluctuation of micro andmacroeconomic factors. The factors comprise of loan to deposit ratio (LDR), capital adequacyratio (CAR), net interest margin (NIM), inflation (INF), interest rate (IR), and exchangerate (ER) consecutively contributed to the variation of non performing loan (NPL)in Indonesian banking sector.